EFEKTIVITAS MODIFIKASI CAKRAM GIZI SEBAGAI MEDIA LINGKARAN STATUS GIZI UNTUK MENINGKATKAN KETERAMPILAN KADER DALAM MENENTUKAN STATUS GIZI BALITA - Wahyu Islami; Agustiansyah Agustiansyah (Pontianak Nutrition Journal (PNJ), 2018)
One of the activities in Posyandu cadres are doing the weighing babies or toddlers. Weight infant or toddler then plotted on Towards Health Card (KMS) to determine if the infant or toddler is growing. Weighing and plotting activities in this KMS is one form of activity assess nutritional status.The important role of Posyandu as the frontline in service to the community, especially toddlers through Posyandu.Already, there is a disc Nutritionlat practical and easy to know the nutritional status and health of children and adults. Can also be used for nutrition education and health in Posyandu, health centers, hospitals or other medical facilities. Category of nutritional status on nutritional disc apparatus 3 that there is an upper limit, ideal, and the lower limit so that in determining the nutritional status determines only normal or not and on disc nutrition there is no way the use of tools. The tObjective of this study is to determine the effectiveness of nutritional modification discs as media circles nutritional status to improve the skills of cadres in determining nutritional status. This type of research is an experiment that was conducted to determine the increase in the skills of cadres before and after using the design of one group pre-test - post-test design. This draft was no comparison group (controls). Take measurements before (pre-test) with anthropometric standard books and do another measurement (post-test) with the media circle nutritional status. Based on the test results Wilcoxcon significant differences between the skillsbefore using the circle tool nutritional status and after using the circle tool nutritional status,with the result of a significant degree (0.000 <0.05) with the difference that a score of 10.67 points. The conclusion of this empirically is There is a significant difference in the improvement of the skills of cadres before and after the study to determine the nutritional status of children. Suggestions that there needs to be more research on the effectiveness of the media in terms of the size of the circle of the status of writing, colors and shapes on the nutritional status of the circle, so that it can be used by volunteers to determine the nutritional status